Thermo-optical liquid-crystal phase modulator for ultrafast optics, driven by neural network - Jullien Aurélie; Ramousse Loic; Barland Stéphane; Femy Vincent; Cheriaux Gilles; Forget Nicolas; Claudet Cyrille (EPJ Web of Conferences)
We propose a new spatial light modulator (SLM) concept, relying on a local thermal modification of a thick liquid crystal layer, that is optically-induced through the absorption of a control beam. This innovative thermo-optically addressed SLM, coined TOA-SLM, has shown dynamic phase control capabilities over multi-octave light spectrum, as a promising candidate for spatial or temporal manipulation of ultrafast pulses. In addition to being ultra-broadband and programmable, such a device is low-cost, large-aperture and un-segmented with a high number of control points. The construction and training of a neural network-based statistical model provides configurable design of a prototype TOA-SLM. This step, together with the ultra-broadband acceptance of the device and its ability to introduce continuous and deep phase modulation over a large aperture, opens the way for ultrafast laser aberration compensation using this new technology.